The notebook [videorecording (DVD)] - Cassavetes, Nick; Gosling, Ryan, 1980-; McAdams, Rachel, 1978-; Garner, James, 1928-2014; Rowlands, Gena; Marsden, James, 1973-; Connolly, Kevin, 1974-; Shepard, Sam, 1943-2017; Thornton, David, 1953-; Allen, Joan, 1956-; Sparks, Nicholas (New Line Home Entertainment, 2005)
Allie Hamilton and Noah Calhoun meet one evening at a carnival. But they are separated by Allie's parents who disapprove of Noah's unwealthy family, and move Allie away. When Allie doesn't hear from Noah after several years, she meets and becomes engaged to a handsome young soldier named Lon. Allie, with her love still alive for Noah, stops by Noah's home to check on him. Seeing that their reunion has rekindled a passionate romance, Allie must now choose between true love and the match that her parents approve of.